Primary Health Care in Preliminary Hypertension Management: A Literature Review - Irvan, Muhammad; Mahfud, Miftakhul Ulum; Mangkuluhur, Adhysta; Faqihudin, Fadli Rizal; Auliansyah, Jundan; Asyari, Rahima Galan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Abstract Purpose: The purpose of the article is to evaluate and emphasize the role of primary health care (PHC) in managing hypertension. It systematically reviews the integration of various pharmacological, non-pharmacological, and technological strategies used in PHC to improve hypertension outcomes. By analyzing studies from different regions and methodologies, the article identifies effective interventions, challenges, and areas requiring improvement in hypertension management. Methodology: This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standard statement. Our search strategy used electronic databases, namely Pubmed, Scopus, and Google Schoolar. Journal searches were conducted in November 2024. Pubmed and Scopus searches used the search keywords "Primary Health Care" OR "Primary Care" AND "Hypertension" AND "Management". Results: Our search strategy identified a total of 2698 articles. After full-text reading, 19 relevant journals were found. Applications/Originality/Value: The article's originality lies in its comprehensive review of primary health care's (PHC) role in managing hypertension, integrating recent evidence (2019–2024) from diverse regions. It highlights the importance of combining medications, lifestyle changes, and technology (e.g., telemonitoring, ABPM) while addressing barriers like poor access, low adherence to guidelines, and socio-economic disparities. By focusing on practical solutions, such as better training, patient education, and programs like Indonesia's PROLANIS, the article offers valuable insights for improving hypertension management, particularly in low-resource settings, emphasizing a holistic, actionable, and globally relevant approach.